Pemikiran Pendidikan Islam Perspektif Azyumardi Azra dan Relevansinya dengan Pendidikan Perguruan Tinggi - Ali Musthafa; M. Yunus Abu Bakar (Pendidikan Agama Islam STIT Palapa Nusantara, 2023)
Islamic education experiences obstacles in its implementation which is inversely proportional to the quantity of Muslims in Indonesia. To overcome these obstacles, people need to understand what kind of concept of Islamic education should be implemented in Indonesia. Various Islamic education figures have interesting views and thoughts on Islamic education, one of which is Azyumardi Azra. This study uses a qualitative approach which aims to analyze and describe the concept of Islamic education from Azyumardi Azra's perspective and its relevance to higher education. The type of research used is library research or research conducted by taking data from literature sources from previous studies. The research results obtained are: Islamic education is a process of forming individuals based on Islamic teachings that originate from the Al-Quran, As-Sunnah, the words of friends, the benefit of the people or social, traditions or customs of society, and the results of the thoughts of experts Islam or ijtihad. The purpose of Islamic education consists of